2013
DOI: 10.1093/jxb/ert332
|View full text |Cite
|
Sign up to set email alerts
|

CEP genes regulate root and shoot development in response to environmental cues and are specific to seed plants

Abstract: The manifestation of repetitive developmental programmes during plant growth can be adjusted in response to various environmental cues. During root development, this means being able to precisely control root growth and lateral root development. Small signalling peptides have been found to play roles in many aspects of root development. One member of the CEP (C-TERMINALLY ENCODED PEPTIDE) gene family has been shown to arrest root growth. Here we report that CEP genes are widespread among seed plants but are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
212
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(233 citation statements)
references
References 40 publications
10
212
1
Order By: Relevance
“…It remains to be determined how the same peptide-receptor module can activate different downstream pathways depending on the root lateral organ considered. Because CEP gene expression is primarily regulated by environmental cues, and notably by N-availability (Delay et al, 2013;Imin et al, 2013), the MtCEP-CRA2 regulatory pathway is likely an important route for plants to control root system architecture in response to environmental influences such as N-availability. The widespread distribution of CEP genes in seed plants and their absence in early plant lineages (Delay et al, 2013;Ogilvie et al, 2014) suggests that CEP-dependent regulatory pathways are likely to operate widely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It remains to be determined how the same peptide-receptor module can activate different downstream pathways depending on the root lateral organ considered. Because CEP gene expression is primarily regulated by environmental cues, and notably by N-availability (Delay et al, 2013;Imin et al, 2013), the MtCEP-CRA2 regulatory pathway is likely an important route for plants to control root system architecture in response to environmental influences such as N-availability. The widespread distribution of CEP genes in seed plants and their absence in early plant lineages (Delay et al, 2013;Ogilvie et al, 2014) suggests that CEP-dependent regulatory pathways are likely to operate widely.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cepr1 phenotypes in Arabidopsis are somewhat different compared to cra2 phenotypes in M. truncatula (Tabata et al, 2014, Huault et al, 2014. In addition, the phenotypic effects of CEP peptides on lateral root and main root growth are different in Arabidopsis and Medicago (Delay et al, 2013;Imin et al, 2013;Tabata et al, 2014). Therefore, modulating CEP pathways may be a way to generate different root system architectures in various plants depending on their environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. truncatula CLE genes were initially annotated by Mortier et al (2010) using Mt2.0, and this was expanded recently to a total of 52 CLE genes by Hastwell et al (2017) using Mt4.0 in their identification pipeline. Studies by Imin et al (2013), Delay et al (2013b), and Ogilvie et al (2014) collectively identified 14 M. truncatula CEP (MtCEP) family members. Noteworthy, seven of the 14 MtCEPs identified in Mt3.5 are missing from Mt4.0, and conversely, a single MtCEP is present solely in Mt4.0.…”
mentioning
confidence: 99%
“…In silico analysis showed that CEP-containing genes occur only in seed plants and are absent in mosses and algae (Ohyama et al, 2008;Delay et al, 2013;Imin et al, 2013;Roberts et al, 2013;Li et al, 2014;Ogilvie et al, 2014). Overexpression of CEP1 in Arabidopsis results in the arrest of root growth (Ohyama et al, 2008), and, in Medicago truncatula, overexpression of CEP1 or application of synthetic CEP1 results in inhibition of lateral root formation, enhancement of nodulation, and the induction of periodic circumferential root swellings Mohd-Radzman et al, 2015).…”
Section: Peptides With Specific Posttranslational Modificationsmentioning
confidence: 99%